Detection of Allergenic Lysozyme during Winemaking with an Electrochemical Aptasensor. Issue 11 (17th July 2019) - Titoiu, Ana Maria; Porumb, Roxana; Fanjul‐Bolado, Pablo; Epure, Petru; Zamfir, Medana; Vasilescu, Alina
Abstract: In this work we investigate the performance of a simple, disposable electrochemical aptasensor for lysozyme and its usefulness for monitoring the allergen risk along wine production. The sensor relies on screen‐printed gold electrodes modified with gold nanoparticles as the electrochemical transducer, with detection by cyclic voltammetry. This simple method is characterized by a detection limit of 0.32 μg.mL −1 lysozyme and a linear range of 1–10 μg.mL −1, being appropriate for the analysis of lysozyme‐treated wines. Several white wines where sulphur dioxide was partially replaced by lysozyme were produced and analyzed with the aptasensor at critical stages during wine production. The results obtained with the aptasensor were moreover compared with those recorded in parallel by a standard method, high performance liquid chromatography (HPLC). The specific advantages brought by the use of nanomaterial and the limitations of the sensor are discussed. The sensor allowed evaluating the effect of various technological steps along wine production on the content of lysozyme. Abstract :